964 Passive monitoring of chemical exposures in south florida firefighters using silicone wristbands. (24th April 2018) - Santiago, Katerina M; Caban-Martinez, Alberto J; Baum, Jeramy; Pangborn, Johnathan; Dikici, Emre; Solle, Natasha Shaefer; Sterling, David A; Moore, Kevin; Grace, Kathy; Daunert, Sylvia; Deo, Sapna; Kobetz, Erin N
Abstract : Introduction: Firefighters are likely to be exposed to many toxic chemicals in the performance of their work duties such as polycyclic aromatic hydrocarbons (PAHs). Chemical exposures may occur through dermal, oral, or inhalation pathways. Passive sampling devices are used to sequester organic molecules through passive diffusion and provide time-weighted averages of chemical concentrations. This pilot study uses silicone-based wristbands as a personal passive sampler to detect known carcinogens during a 24 hour work shift. Methods: Twenty-four wristbands were deployed across various fire services throughout South Florida. Prior to deployment, bands were cleaned using a standardised cleaning protocol to remove contamination and optimise the surface for absorption. Wristbands were then packaged in air-tight bags to prevent contamination. Wristbands were worn on fire service personnel and collected at the end of a 24 hour work shift. Chemical contaminants were then extracted from the wristband and analysed for PAHs—identified using the EPA IRIS, California Proposition 65, and IRAC datasets—using gas chromatography-mass spectrometry. Results: The average number of chemicals found across all wristbands (n=24) was 23 with 4 categorised as carcinogenic to humans (i.e., Benzo[b]fluoranthene, Benzo[j]fluoranthene, Chrysene, and Naphthalene). All bands had at least one PAH present, specifically, 87.5% contained Benzo[b]fluoranthene (mean=5.23 ng/band), 50% contained Benzo[j]fluoranthene (mean=2.05 ng/band), 79.2% contained Chrysene (mean=9.55 ng/band), and 100% contained Napthalene (mean=176.53 ng/band). Actual types of exposure compounds is likely to be larger than the observed data as the group of PAHs detected was limited to three existing datasets. Discussion: Silicone-based wristbands are feasible to use within the fire service to detect and characterise ambient hazardous chemical compounds. These personal self-samplers used during a 24 hour collection period identified various PAHs in the firefighter work environment. Objective measures of harmful chemical exposures in the fire service should be monitored with a comprehensive surveillance system that includes personal sampler devices.